Numerical study of the segmental tunnel lining behavior under a surface explosion – Impact of the longitudinal joints shape. (December 2020) - Rashiddel, Alireza; Kharghani, Mehdi; Dias, Daniel; Hajihassani, Mohsen
Abstract: In recent years, the vulnerability and protection of subsurface structures under blast loads became a fundamental issue in terms of security (loss of lives and structural damage). A tunnel can be considered as an underground shelter and is a crucial structure owing to its conservative nature against explosions. This study is performed to obtain a further understanding of surface explosion influence on segmental tunnels. In this paper, a tunnel lining and its segmentation with planar and curved joints under dynamic loads were investigated. In this regard, a 2D finite-deference simulation of the Tehran metro segmental lining was conducted. Subsequently, an explosion wave stress of 500 kg of TNT explosive was considered as the reference loading case. The results indicated that the segmental lining with curved joints is efficient and succeeds in neutralizing the surface explosion. The maximum bending moments and axial forces in the curved segmental lining are lower than in the planar segmental and continuous lining. In terms of vertical and horizontal displacements of the tunnel lining, the segmental structure with curved joints induces the minimum deformation amount. The continuous lining and planar segmental lining show instability under the reference blast load. Finally, it can be concluded that the segmental lining with curved joints is highly efficient and stable in case of a surface explosion.